Case report: Thrombolysis in patients with acute ischemic stroke and cerebral cavernous malformation - Lin, Jie; Weng, Xiongpeng; Zheng, Jing; Wu, Saizhen; Bao, Qiongqiong; Peng, Feifei; Huang, Yanbin (Frontiers in Neurology, 2023)
Background: Cerebral cavernous malformation (CCM) is a rare disease associated with a latent risk of intracranial hemorrhage. However, due to limited evidence, the safety of recommending intravenous tissue plasminogen activator for patients with acute stroke and CCM remains uncertain. Methods: Our study identified five patients with acute stroke and CCM treated between 2017 and 2023 across two hospitals. A comprehensive literature review was conducted, incorporating three similar case reports and two retrospective studies. Results: Among 30 patients reviewed, three exhibited symptomatic intracranial hemorrhage, two of whom were female. Additionally, three patients presented with calcification in their CCM, with two experiencing symptomatic intracranial hemorrhage. Conclusions: The observed incidence of symptomatic intracranial hemorrhage following intravenous tissue plasminogen activator administration appears to be elevated in patients with CCM. Therefore, before thrombolysis, a thorough evaluation of personalized risk-benefit ratios is crucial. Furthermore, conducting further research involving multiple centers and larger sample sizes is imperative to advance our understanding in this area, especially, identifying hemorrhage risk factors.